2013
DOI: 10.4103/2229-5070.122127
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of Taenia asiatica in humans and animals

Abstract: Taenia asiatica is a recently described species known to cause intestinal teniasis in humans and cysticercosis in animals. This species has close morphological resemblance to Taenia saginata and has a life cycle resembling Taenia solium, hence has been posing diagnostic dilemma and had been the reason for its comparatively late discovery. Recent diagnostic tools such as serological and molecular techniques have thrown light on its exact prevalence in the endemic countries. Hence introduction of utilization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…According to the previous studies reported in the literature regarding the morphology of T. asiatica , the number of uterine branches of proglottids varied between 11-31 ( 4 ) and other reported it was between 16-21 ( 5 ). Our finding in this study showed that the number of uterine proglottids of T. asiatica from Simalungun was constant, which was 16 branches.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…According to the previous studies reported in the literature regarding the morphology of T. asiatica , the number of uterine branches of proglottids varied between 11-31 ( 4 ) and other reported it was between 16-21 ( 5 ). Our finding in this study showed that the number of uterine proglottids of T. asiatica from Simalungun was constant, which was 16 branches.…”
Section: Discussionmentioning
confidence: 95%
“…They reported that the number of uterine branches of gravid proglottids was between 16-21, and scolex has a rostellum ( 5 ). Parija and Pnombath in 2013 reported that the number of uterine branches with different variation, which was between 11-31 and scolex has a rostellum and apical pit ( 4 ). Our finding, upon light microscope examination with 100x and 400x magnification, there was no rostellum or apical pit found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosa laboratorium untuk identifikasi taeniasis pada umumnya dilakukan dengan menggunakan metode morfologi, yaitu dengan cara menemukan telur dan proglatid pada sampel feses penderita. Pada metode morfologi, dapat digunakan pewarna untuk mengamati morfologi telur atau proglatid, yaitu pewarna Ziehl-Neelsen dan Hematoxylin-Eosin (Parija & Ponnambath, 2013). Penelitian yang dilakukan oleh Wandra, dkk (2011), menyebutkan bahwa masih terdapat potensi endemik taeniasis di Bali.…”
Section: Pendahuluanunclassified
“…On the other hand, the eggs hatched in the human intestine can finally produce the cysts in areas with high blood flow such as CNS (neurocysticercosis), the muscles (human cysticercosis), the subcutaneous tissue and the eye (subcutaneous and ocular cysticercosis, respectively) [5,8]. Taenia asiatica, also known as Asian Taenia, similar to T. saginata is responsible for intestinal teniasis and has been identified in several Asian countries [3,9]. Cysticercus fasciolaris is the larval stage of the cestode T. taeniaeformis in wide variety of small rodents, and occasionally birds and humans, as intermediate hosts with cats as the definitive hosts [10].…”
mentioning
confidence: 99%